Parent and Teacher Collaboration in Home Education: Challenges, Opportunities, and Insights - Luisito M. Nanquil (Bina Nusantara University, 2021)
The research aimed to analyze how parents and children dealt with home education as well as its effectiveness. On the so-called new normal, many impediments and disruptions came to the lives of stakeholders. Thousands of schools were forced to shut down due to financial constraints and/or issues. Parents had thought of finding an alternative way to continue with the schooling of their children. In the Philippines, a modular approach was introduced, representing the home education/schooling type of instruction. This was the purpose of the research. Five parents served as the participants of the research in which ethnography was used as its qualitative approach. It is found that homeschooling and education are proved to be responsive and relevant to many people due to tangible benefits and perks enjoyed by the learners and parents. On the other hand, parents and children also see and experience some challenges in doing the modules’ requirements. It is advised that parents, children (learners), and teachers need to work in collaboration for the successful outcomes of homeschooling. Another issue is how parents should perform an assessment with their children as learners. However, teachers should not only be there for online consultation. This method of teaching and learning is still in the process of adjustment, but soon people involved in this paradigm will realize its value and role in today’s global education and situation.